2017
DOI: 10.1055/s-0037-1607060
|View full text |Cite
|
Sign up to set email alerts
|

Patient Factors Associated with Failure of Flap Coverage Used during Revision Total Knee Arthroplasty

Abstract: Revision total knee arthroplasty (rTKA) is a challenging problem in the setting of soft tissue defects. The purpose of this study was to evaluate patients who underwent rTKA requiring flap coverage and determine patient factors that predisposed them to failure. Forty-three consecutive patients (mean follow-up, 46.5 months) who underwent rTKA requiring flap coverage were retrospectively reviewed between January 1, 2000 and December 31, 2010. Sixteen of 43 patients experienced failure requiring either flap revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(20 reference statements)
1
7
1
Order By: Relevance
“…In our study, functional knee joint salvage was achieved in 80.6% of patients in the EC group, with four (12.9%) eventually having to have knee joint fusion and only two (6.5%) requiring transfemoral amputation. These results are superior to previously reported results, as functional knee joint salvage was achieved in 54% to 64% of cases and incidence of transfemoral amputation ranged from 16% to 33% after complicated TKA and flap reconstruction 4,7,8,16 (Supplement 1). This improved rate of functional joint salvage highlights the need for MDT approach for both surgical planning and execution.…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, functional knee joint salvage was achieved in 80.6% of patients in the EC group, with four (12.9%) eventually having to have knee joint fusion and only two (6.5%) requiring transfemoral amputation. These results are superior to previously reported results, as functional knee joint salvage was achieved in 54% to 64% of cases and incidence of transfemoral amputation ranged from 16% to 33% after complicated TKA and flap reconstruction 4,7,8,16 (Supplement 1). This improved rate of functional joint salvage highlights the need for MDT approach for both surgical planning and execution.…”
Section: Discussioncontrasting
confidence: 80%
“…Lastly, studies on the type of microbial pathogen responsible for the PJI and the proximal placement technique success rate thereafter would be of particular interest considering recent published data has found specific microbial organisms to be more devastating to the well-being of a joint revision than others. 38 In conclusion, we believe this novel proximal placement of the knee joint in patients with a PJI-K who have large anterior soft tissue defects lessens the need for free flaps in patients that would have otherwise required them. Furthermore, the reattachment of the quadriceps mechanism to the proximal tibia, can provide enough extensor power to lock the hinge mechanism of the total joint in gait cycle.…”
Section: Discussionmentioning
confidence: 79%
“…Two senior authors independently reviewed the titles and abstracts to screen for only those that investigated the use of flap coverage following TKA. To offer a review of the highest caliber of evidence available, reports were included if they were: (1) case series, (2) level III studies or above (including retrospective cohort studies and meta-analyses), (3) in English, and (4) discussed the outcome of graft or flap coverage of soft tissue defects after TKA. Reports were excluded if they were: (1) case reports and review articles, (2) in languages other than English, (3) expert opinion pieces, or (4) failed to describe outcomes of grafts or flaps following TKA.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the authors found that patients with heart failure, cancer, and infection with Klebsiella pneumoniae remain significantly more likely to undergo either flap revision or above the knee amputation. 3 In another case series, Corten et al followed 24 patients for a mean of 4.5 years (range, 1-10 years) who underwent gastrocnemius flap coverage, and 92% eventually obtained a satisfactory result. The gastrocnemius flap was used reliably and safely to treat complex wounds, where infection control, retention of the prosthesis and functional recovery were the primary concerns.…”
Section: Gastrocnemius Flapsmentioning
confidence: 99%
See 1 more Smart Citation